Effect of High Dose Methylprednisolone in Near Hanging Patients: A Retrospective Observational Study in a Tertiary Level Private Hospital in Bangladesh - A K M Ferdous Rahman; Saifullah Al Kafi; Sabrina Sultana; Zubaer Wasit Nasif; Dipok Das (Bangladesh Critical Care Journal, 2024)
Background: In the context of Bangladesh, hanging stands out as a notable method of suicide. This study focuses on patients who presented with near hanging, assessing their clinical profile, response to early management protocol and their outcome. Method: Spanning from January 1 to December 31, 2023, this retrospective study delves into the records of 10 Bangladeshi patients who engaged in near hanging. Demographic, clinical, and treatment particulars were collected along with initiation of early management protocol with an emphasis on the administration of high-dose methylprednisolone. The study evaluates the outcomes, including length of stay in the intensive care unit (ICU), and the need for intubation & mechanical ventilation, and in hospital mortality. Results: Within the specified sample size of 10 patients, comprising 30% men with a median age of 18 (range: 14–40), admission data revealed that 20% of patients had a Glasgow Coma Scale of ≤8, 10% exhibited hypotension, and no patient experienced hanging-induced cardiac arrest. All patients received high-dose methylprednisolone to reduce inflammation and oedema in injured spinal cord. Notably, a positive neurological outcome was observed in 90% of patients, with no reported mortality. The median length of stay in the ICU was 3 days, and only 10% of patients required intubation. Conclusion: The administration of high-dose methylprednisolone resulted in favourable outcomes. The study showed a zero-mortality rate, a median ICU stay of 3 days, and a 10% requirement for intubation. These findings emphasize the potential efficacy of high-dose methylprednisolone in managing near hanging cases in the Bangladeshi population, offering insights for future interventions and research. Bangladesh Crit Care J March 2024; 12 (1): 35-40